PENGARUH SISTEM PENGENDALIAN INTERN, SISTEM INFORMASI AKUNTANSI, DAN KOMPETENSI APARAT TERHADAP AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA: STUDI EMPIRIS DESA-DESA DI KABUPATEN ROKAN HULU - Wahyuni, Siska; Indrawati, Novita; Azhar A, Al (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
This study aims to examine the influence of internal control system, accounting information system, and apparatus competencies on the accountability of village fund allocation management.The population in this study were 145 villages in Rokan Hulu Regency. In this study, the sample used were 106 villages selected by using accidental sampling method. This study used primary data by distributing questionnaires. The analytical method used in this study was multiple linear regression analysis. The results of this study indicate that the internal control system has a positive effect on the accountability of village fund allocation management, the accounting information system has a positive effect on the accountability of village fund allocation management and the competency of the apparatus has a positive effect on the accountability of village fund allocation management.